Third World food markets: option for agricultural exporters? - International Food Policy Research Institute (International Food Policy Research Institute, 1988)
What are the characteristics and conditions of growth in Third World food markets? Under what circumstances is agricultural growth in developing countries consistent with the interests of developed, food-exporting countries? What measures, national and international, are necessary to promote agricultural and overall growth in developing countries in a manner mutually beneficial to developed and developing countries, in the context of an expanding world economy? This paper seeks to throw light on these and related questions.